(3QSGdI aj GdScfLHjfs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf SGdJ CHGSYjO , CSYOc Gddg, aj LejY CehQc, Cf CQSe dc efGaY GdTQGH deSej ScfLHjfaCfG aGYd Pdc HeTjFI Gddg JYGdi s
(3BNQgG (B:s
(3hbO PcQfGg eGSCdJfG hGdEfGA Yfg hdhGgH GdYbd GdMeO HdG fgGjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B106 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B263 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(2119) s
Keywords: (3GdWHs